Ice and snow thickness of the IGAN Glacier in the Polar Urals from ground-based radio-echo sounding 2019 and 2021 - I. Lavrentiev I.; G. Nosenko A.; A. Glazovsky F.; A. Shein N.; M. Ivanov N.; Ya. Leopold K.; И. Лаврентьев И.; Г. Носенко А.; А. Глазовский Ф.; А. Шеин Н.; М. Иванов Н.; Я. Леопольд К. (DEStech Transactions on Computer Science and Engineering, 2023)
Small glaciers of the Polar Urals are at the limits of their existence. Their state and changes serve as an important natural indicator of modern climatic changes. In 2019 and 2021, we performed ground-based radar studies of one of these glaciers, the IGAN Glacier, to measure ice thickness and snow cover. We used PicorLed (1600 MHz), and VIRL–7 (20 MHz) GPRs. According to these data, the glacier has an average thickness of 49 m, maximum 114 m. The glacier has a polythermal structure: a cold ice layer with an average thickness of 12 m (maximum 43 m), overlaps the temperate ice with an average thickness of 37 m (maximum 114 m in the upper part of the glacier). The volume of ice contained in the glacier (in its studied part) is 14.3 × 106 m3, of which 10.89 × 106 m3 is temperate ice and 3.44 × 106 m3 is cold ice. For comparison: according to the radar data of 1968, the total ice thickness then reached 150 m in the central part, and the thickness of the upper layer of cold ice was 40–50 m. Radar snow gauge survey allowed to build schemes of seasonal snow thickness distribution over the glacier surface in 2019 and 2021, where there is a general spatial pattern of snow thickness growth from 2 m on the glacier terminus to 8 m or more to the rear wall of the corrie, which is due to the significant influence of avalanche feeding and wind transport. The glacier has lost about 3.2 × 106 m3 of ice per last decade, if the rate of loss continues, it may disappear in 40–50 years. However, this process may have a non-linear nature, as it involves not only climatic factors, but also local terrain features, on the one hand contributing to a high accumulation of snow, on the other – the formation of a glacial lake during glacier retreat, which may increase ablation. В 2019 и 2021 гг. на леднике ИГАН проводились георадарные измерения толщины льда (ВИРЛ-7, 20 МГц) и снежного покрова (Пикор-Лёд, 1600 МГц). Показано, что ледник имеет политермическую структуру, а его толщина достигает 114 м. Выполнена оценка величины и особенностей ...